2015
DOI: 10.1073/pnas.1513754112
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, causes, and consequences of marine larval dispersal

Abstract: Quantifying the probability of larval exchange among marine populations is key to predicting local population dynamics and optimizing networks of marine protected areas. The pattern of connectivity among populations can be described by the measurement of a dispersal kernel. However, a statistically robust, empirical dispersal kernel has been lacking for any marine species. Here, we use genetic parentage analysis to quantify a dispersal kernel for the reef fish Elacatinus lori, demonstrating that dispersal decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
194
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(202 citation statements)
references
References 45 publications
6
194
2
Order By: Relevance
“…Our results are in broad agreement with two studies on coral groupers and snappers from the Great Barrier Reef 24 and Manus Island 26 that identified dispersal events up to 30 km away from spawning locations. However, a recent study 25 found that a pelagic-spawning goby inhabiting sponges on the Belize barrier reef with a larval duration of 18-34 days had a median dispersal distance of only 1.8 km, an order of magnitude lower than our estimates for A. percula, which spawn demersal eggs and have a much shorter pelagic larval duration (PLD). Marine reserves would need to be placed considerably closer together than is commonly achieved if the results from gobies in Belize are the rule rather than the exception and dispersal distances are commonly less than 10 km in coral-reef fishes.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Our results are in broad agreement with two studies on coral groupers and snappers from the Great Barrier Reef 24 and Manus Island 26 that identified dispersal events up to 30 km away from spawning locations. However, a recent study 25 found that a pelagic-spawning goby inhabiting sponges on the Belize barrier reef with a larval duration of 18-34 days had a median dispersal distance of only 1.8 km, an order of magnitude lower than our estimates for A. percula, which spawn demersal eggs and have a much shorter pelagic larval duration (PLD). Marine reserves would need to be placed considerably closer together than is commonly achieved if the results from gobies in Belize are the rule rather than the exception and dispersal distances are commonly less than 10 km in coral-reef fishes.…”
Section: Discussioncontrasting
confidence: 92%
“…Although reef fish larvae clearly have the potential for long-distance movements 14 , there is increasing evidence that dispersal may be more limited than previously assumed 15,16 . The most compelling evidence of larvae returning to natal or nearby reefs has come from chemical labelling of embryos 17,18 and genetic DNA parentage analyses [19][20][21][22][23][24][25][26][27] . However, few studies have been able to fully describe a dispersal kernel by determining the distances over which spatially fragmented subpopulations are connected by larval movements.…”
mentioning
confidence: 99%
“…As no large‐scale AEM was detected as significant, genetic variation at broad scale cannot be explained by passive larval dispersal. At such scale, genetic connectivity could result from processes such as adult mobility, demographic history, or multigenerational stepping stone larval dispersal (D'Aloia et al., 2015) that were not tested in our analyses. Larval dispersal is therefore expected to be better correlated to genetic variation at smaller scales, corresponding to the distances larvae can travel during 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown based upon larval recruitment back into a reserve (Harrison et al 2012, Almany et al 2013, microchemistry (Chittaro & Hogan 2013), and population genetics (Christie et al 2010, D'Aloia et al 2015. However, the shape and function of a larval dispersal network can change, depending on the species (Holstein et al 2014) and the timescales (Kough & Paris 2015) being considered.…”
Section: Introductionmentioning
confidence: 99%